Pengembangan Sistem Informasi Pengelolaan Perpustakaan (Automasi Perpustakaan) Pada SMP Negeri 1 Padang Ganting - Dodi Nofri Yoliadi (IAIN Batusangkar, 2022)
Many libraries have developed services in information systems to facilitate library management. The purpose of this information system is to optimize the performance of library services. In Padang Ganting 1 Public Middle School, providing services for searching, borrowing, and returning books to the library is still manual, so it is necessary to develop an information system in the form of a library automation system. The information system is designed using a programming language, which is software that makes it easy to manage procedures or mechanisms in the library, such as borrowing, searching, returning, and developing, with an automated system. A library information system is available to assist in managing the library electronically so that it is easier for the library to record every data transaction contained in the library.